An NMR Metabolomics Approach and Detection of Ganoderma boninense-Infected Oil Palm Leaves Using MWCNT-Based Electrochemical Sensor. (19th June 2019) - Isha, Azizul; Akanbi, Fowotade Sulayman; Yusof, Nor Azah; Osman, Rosiah; Mui-Yun, Wong; Abdullah, Siti Nor Akmar
Abstract : Ganoderma boninense ( G. boninense ) has been identified as a major problem in oil palm industry which caused basal stem rot disease. Identification of metabolite variation of healthy and G. boninense -infected oil palm leaves at 14 days postinfection using NMR metabolomics approach followed by characterization of an electrochemical sensor based on a functionalized multiwalled carbon nanotube (MWCNT) layer-by-layer framework on modified screen-printed carbon electrode has been successfully determined. Significant differences from the 1 H NMR data were observed between healthy and G. boninense -infected oil palm leaves, according to principal component analysis. Gold nanoparticle-functionalized MWCNT and chitosan-functionalized MWCNT were deposited on a screen-printed carbon electrode and were applied for the electrochemical detection of healthy and G. boninense -infected oil palm leaves. The electrocatalytic activities of a modified electrode towards oxidation of healthy and G. boninense -infected oil palm leaves at a concentration of 100 mg/L were evaluated using cyclic voltammetry and linear sweep voltammetry. The limits of detection of healthy and G. boninense -infected oil palm leaves were calculated to 0.0765 mg/L and 0.0414 mg/L, respectively. The modified electrode shows a good sensitivity and reproducibility due to the unique characteristics of gold nanoparticles, chitosan, MWCNTs, and synergistic interaction between them.